In vivo imaging of epileptic foci in rats using a miniature probe integrating diffuse optical tomography and electroencephalographic source localization - Yang, Hao (Epilepsia, 2014)
OBJECTIVE: The goal of this work is to establish a new dual-modal brain mapping technique based on diffuse optical tomography (DOT) and electroencephalographic source localization (ESL) that can chronically/intracranially record optical/EEG data to precisely map seizures and localize the seizure onset zone and associated epileptic brain network. METHODS: The dual-modal imaging system was employed to image seizures in an experimental acute bicuculline methiodide rat model of focal epilepsy. Depth information derived from DOT was used as constraint in ESL to enhance the image reconstruction. Groups of animals were compared based on localization of seizure foci, either at different positions or at different depths. RESULTS: This novel imaging technique successfully localized the seizure onset zone in rat induced by bicuculline methiodide injected at a depth of 1mm, 2mm and 3mm, respectively. The results demonstrated that the incorporation of the depth information from DOT into the ESL image reconstruction resulted in more accurate and reliable ESL images. Although the ESL images showed a horizontal shift of the source localization, the DOT identified the seizure focus accurately. In one case, when the BMI was injected at a site outside the field of view (FOV) of the DOT/ESL interface, ESL gives false positive detection of the focus while DOT shows negative detection. SIGNIFICANCE: This study represents the first to identify seizure onset zone using implantable DOT. In addition, the combination of DOT/ESL has never been documented in neuroscience and epilepsy imaging. This technology will enable us to precisely measure the neural activity and hemodynamic response at exactly the same tissue site and at both cortical and sub cortical levels.